2016
DOI: 10.1089/jmf.2015.3540
|View full text |Cite
|
Sign up to set email alerts
|

Perilla frutescensExtract Ameliorates Acetylcholinesterase and Trimethyltin Chloride-Induced Neurotoxicity

Abstract: One of the critical features of Alzheimer's disease is cognitive dysfunction, which is, in part, due to decreases in acetylcholine (ACh). The ethanol extract of Perilla frutescens was selected for isolating the acetylcholinesterase (AChE) inhibitor based on preliminary screening. In vivo behavioral tests were performed to examine the effects of the P. frutescens extract on trimethyltin chloride-induced impairment of learning and memory in mice. A diet containing P. frutescens extract effectively reversed learn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…TMT induces neuronal degeneration in the hippocampus, and results in behavioral alterations, including cognitive impairment. TMT has been widely used as a neurotoxin based on its in vivo behavioral changes and biochemical effects in the brain [9]. In agreement with many other previous studies, our study confirmed that TMT induced learning and memory impairment in mice.…”
Section: Ache Activity and Ach Content In Mouse Brain Tissuesupporting
confidence: 92%
“…TMT induces neuronal degeneration in the hippocampus, and results in behavioral alterations, including cognitive impairment. TMT has been widely used as a neurotoxin based on its in vivo behavioral changes and biochemical effects in the brain [9]. In agreement with many other previous studies, our study confirmed that TMT induced learning and memory impairment in mice.…”
Section: Ache Activity and Ach Content In Mouse Brain Tissuesupporting
confidence: 92%
“…Perilla is a self-pollinating plant and widely distributed in East Asian countries and considered as a food supply and natural medicine resource [ 1 , 2 ]. Perilla frutescens belongs to the Lamiaceae family and encompasses many natural varieties [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similar to the results of α‐glucosidase inhibitory, the AChE inhibitory was only significantly related to TPC ( r = −0.605, p < .05) and FRAP ( r = −0.647, p < .05), while the correlations to TFC, DPPH scavenging activity, and ABTS + scavenging ability were all not significant ( p > .05). The reason might be that although phenolic compounds, especially rosmarinic acid was identified as the major AChE inhibitor in P. frutescens (Choi et al., 2016), other uncharacterized components in this study, including perilla aldehyde, water‐soluble components, and others, also played important role in the AChE inhibitory (Park et al., 2016; Um et al., 2013), and they had different correlations with antioxidant activities.…”
Section: Resultsmentioning
confidence: 78%